2012
DOI: 10.1002/ange.201108580
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Dependent Acidity and Photocatalytic Activity of Nb2O5 Nanocrystals with an Active TT (001) Surface

Abstract: The search for new low carbon and clean energy technologies is prominent on the research agendas of many governments, universities, and industrial sectors. In particular, the possibility of using solar energy for hydrogen production, fine chemicals manufacture, and water cleansing is currently under intense research. The use of semiconducting oxides, such as TiO 2 and ZnO, as photoactive materials has been receiving much attention. Recent work indicates that nanoparticles of these compounds show strong shape-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 19 publications
(19 reference statements)
3
29
0
1
Order By: Relevance
“…However, the Nb peak can be deconvoluted into two peaks with binding energies of 207.2 eV and 205.8 eV, and are assigned to Nb 5+ and Nb 4+ , respectively. This agrees well with the reported literature values (207.0 to 207.6 eV for Nb 3d5/2 in Nb 2 O 5 and 205.2 to 206.1 eV for Nb 3d5/2 in NbO 2 according to the NIST database)3243. Furthermore, these results also suggest that there are small amounts of suboxide species such as NbO 2 in the Nb 2 O 5 , in accordance with the EDS stoichiometric Nb 2 O 4.8 composition.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, the Nb peak can be deconvoluted into two peaks with binding energies of 207.2 eV and 205.8 eV, and are assigned to Nb 5+ and Nb 4+ , respectively. This agrees well with the reported literature values (207.0 to 207.6 eV for Nb 3d5/2 in Nb 2 O 5 and 205.2 to 206.1 eV for Nb 3d5/2 in NbO 2 according to the NIST database)3243. Furthermore, these results also suggest that there are small amounts of suboxide species such as NbO 2 in the Nb 2 O 5 , in accordance with the EDS stoichiometric Nb 2 O 4.8 composition.…”
Section: Resultssupporting
confidence: 92%
“…It has been reported that Nb 2 O 5 exhibits a different decomposition mechanism from the conventional radical-produced process. With regard to the strong adsorption of dye molecules, it seems that the dye molecules are immobilized at the solid acid sites, where the photoinduced electrons and holes on the surface can attack dye species without producing any radicals32. Therefore, the higher adsorbed amounts of dye molecules as well as the bigger surface-to-volume ratio of Nb 2 O 5 nanoplates lead to the higher degree decomposition of dyes than commercial Nb 2 O 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5b). The two peaks could be ascribed to Nb–F chemical bonding20. The peaks of NOF at around 529.54 and 683.74 eV can be ascribed to O1s corresponding to typical Nb-O band and F1s corresponding to typical Nb-F band (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…[18][19][20] Recently, the activity of Nb 2 O 5 was shown to be closely associated with its shape and surface structure. [21][22][23][24][25] In particular, nanorods of Nb 2 O 5 were prepared and shown to possess superior properties in various applications including humidity sensor, 21 powerful catalysts for vanadium redox flow battery, 22 high performance dye-sensitized solar cells, 23 biosensor, 24 etc. However, Nb 2 O 5 nanocrystals remain less explored as a photocatalyst presumably due to its rather wide band gap that makes it active in the UV region alone, therefore restraining the practical use of Nb 2 O 5 to ≤5%.…”
mentioning
confidence: 99%